2008
DOI: 10.1111/j.1442-2050.2008.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cyclooxygenase-2 is associated with chemoradiotherapy resistance and prognosis in esophageal squamous cell carcinoma patients

Abstract: Our objective was to investigate whether cyclooxygenase-2 (COX-2) expression can predict the patient's response to chemoradiotherapy (CRT) and ensuing prognosis in esophageal squamous cell carcinoma (ESCC). The clinicopathological and follow-up data of 112 patients with ESCC who underwent CRT from January 2001 to June 2006 were analyzed retrospectively. The immunohistochemical expression level of COX-2 was examined for all biopsy specimens of primary tumors, and the correlation of COX-2 expression with the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 20 publications
3
26
0
1
Order By: Relevance
“…Several groups have previously failed to detect any correlation with survival, whereas others have found a correlation between COX-2 and survival, but only in a nonindependent manner or in patients with advanced disease. 48,55,56 Niesporek et al, 49 by combining descriptive observations of tumor tissues with data from cell cultures, previously presented evidence suggesting that COX-2 overexpression in prostate carcinoma is attributable to deregulated HuR activity. Indeed, mutated HuR has never previously been identified in cancer, but it influences the expression of target mRNAs that encode for genes fundamental to the acquisition of a tumor phenotype, such as the genes involved in the cell cycle and apoptosis regulation, in angiogenesis and migration, and in the evasion of immune recognition.…”
Section: Discussionmentioning
confidence: 93%
“…Several groups have previously failed to detect any correlation with survival, whereas others have found a correlation between COX-2 and survival, but only in a nonindependent manner or in patients with advanced disease. 48,55,56 Niesporek et al, 49 by combining descriptive observations of tumor tissues with data from cell cultures, previously presented evidence suggesting that COX-2 overexpression in prostate carcinoma is attributable to deregulated HuR activity. Indeed, mutated HuR has never previously been identified in cancer, but it influences the expression of target mRNAs that encode for genes fundamental to the acquisition of a tumor phenotype, such as the genes involved in the cell cycle and apoptosis regulation, in angiogenesis and migration, and in the evasion of immune recognition.…”
Section: Discussionmentioning
confidence: 93%
“…Although most of the studies in this analysis consisted of univariate analysis and pooling results of these studies may lead to bias, this finding is important for the clinical application and further prospective studies of COX-2 in ESCC. Interestingly, Huang et al 33 demonstrated that COX-2 expression in pre-treated biopsy specimens was associated with chemoradiation therapy resistance and poor prognosis in ESCC patients and Li et al 36 found that COX-2 expression predicts treatment outcome of prostate cancer. It should be noted that some important studies had to be excluded from our analysis; these included studies concerning COX-2 expression with neoadjuvant therapy of oesophageal cancer and subgroup study.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen were dealing with clinicopathological factors, 12 were with OS. Four publications 22,[33][34][35] investigated the association between COX-2 expression and patients' response to chemoradiotherapy; because of small size and different protocol, these studies were not included in our study. There were mainly two kinds of methods for the evaluation of COX-2 expression in oesophageal cancer specimens: immunohistochemistry (IHC) and in situ hybridization (ISH); in some studies, western blotting or RT-PCR was used in a part of specimens and hence, they were excluded from this study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the case of heavily pretreated recurrent ovarian cancer, the administration of celecoxib in combination with carboplatin-based chemotherapy also yielded promising results (154). The discrepancy in various results may be due to multiple factors, such as complex pharmacodynamic interactions between NSAIDs and the cytotoxic drugs and the varying levels of intratumoural COX-2 and ABC transporters (155)(156)(157)(158)(159). The role of COX-2 expression in the response of cancer cells to combined NSAID and antitumour drug therapy was demonstrated by Edelman et al and has been supported by other studies (155,160).…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Clinicamentioning
confidence: 99%